Energy Audit of Sardar Patel College, Chandrapur, Central India - Kamble, Prashik P; Kamble, Rahul K (International Journal of Environment, 2014)
Energy audit of Sardar Patel College was carried out in 2012-2013. Energy audit of the college revealed that annual electricity consumption was 93,984 units at a total cost of Rs 8,28,248/- (US$ 15059) with an average of Rs 8.66 (US$ 0.15) per unit. The per capita energy expenditure on a student comes out to be Rs 127.42/- (US$ 2.31) per annum, while including teaching and non-teaching faculty members it was Rs 121.80/- (US$ 2.21) per annum. To reduce the electricity consumption in the college various measures were suggested such as use of energy efficient appliances, task lighting, peak shaving and good housekeeping measures. DOI: http://dx.doi.org/10.3126/ije.v3i3.11062 International Journal of Environment Vol.3(3) 2014: 36-49